Exploring The VAW method of writing: application of scaffolding theory in improving writing skills - Wardatul Akmam Din; Asmaa AlSaqqaf; Dg Nursazwani Daud (2018)
This paper reviews how the application of scaffolding theory could develop the method or module of writing. The problem of ESL pupils in Malaysia includes the hitches in understanding word implication and meaning, vocabulary as well as writing skills. Apparently, there is a difference between writing in the first and the second language. This paper proposes a method of writing with a module i.e. the VAW Method which is concentrating on vocabulary enrichment in order to develop young learners’ writing skills. The VAW method contains of vocabulary enhancement (V), application and practice (A) as well as Writing (W). It is expected to assist learners on developing the skills of writing academically. However, this method or module can only be implemented successfully by utilizing the cognitive process theory and most prominently the scaffolding theory in the process of writing. In education, scaffolding can be defined as a variety of instructional techniques practiced by the practitioners and educators in increasing pupils’ understanding and eventually independence in the process of learning. Scaffolding is deliberated as a crucial element of effective teaching and learning to L2 primary school pupils which is commonly practiced in fulfilling the learning gaps i.e., the variance between what pupils have learned and what they are expected to know and do at a certain point in their learning.